Dispersion and Storage Coefficient Influence on Accumulation of Frankia Transport in Heterogeneous Silty and Fine Sand Formation, Warri, Delta State of Nigeria - F. E., Ezeilo; S. N., Eluozo (International Journal For Research In Mechanical & Civil Engineering, 2018)
The study of frankia transport pressured by dispersion and storage coefficient has been thoroughly expressed. The study has monitored the deposition of frankia in silty and fine sand formation. The developed model has express the behaviour of frankia in the study location, storage coefficient and dispersions were observed to pressure the behaviour of the contaminant as expressed in graphical representation, the fluctuation of concentration reflect the influences from porosity variation thus dispersion and storage coefficient, this generated slight accumulation of frankia in silty and fine sand formation, this condition were examined through the rate of its deposition base on some fluctuation experienced that could not monitor the detail deposition of frankia transport in silty and fine sand formation, slight heterogeneous setting in the formation were also observed, the developed model were compared with other experimental values, and both parameters expressed favourable fits validating the model.